KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN GURU DI SEKOLAH (STUDI KASUS DI SDN RANCAEKEK 05 KABUPATEN BANDUNG) - Muthia, Derifa Siti; Hidayat, Ayi Najmul; Agustendra, Apen; Lestari, Rahayu Dwi (STKIP Pesisir Selatan, 2025)
This study aims to gain an in-depth understanding of the role of transformational leadership of school principals in improving teacher discipline in elementary schools. The background of this research is the importance of teacher discipline in creating a positive school culture and quality learning, despite the fact that some teachers remain inconsistent in complying with school rules and carrying out their duties properly. This research employed a descriptive qualitative approach conducted at SD Negeri Rancaekek 05, Bandung Regency. Data were collected through in-depth interviews, participatory observations, and documentation. Informants included the school principal, teachers, and educational staff, selected through purposive sampling. Results: The findings reveal that principals who adopt transformational leadership styles are able to improve teacher discipline through four key dimensions: serving as role models (idealized influence), inspiring motivation and vision (inspirational motivation), encouraging innovation (intellectual stimulation), and providing individualized support (individualized consideration). This leadership approach emphasizes not only adherence to rules but also the internal motivation of teachers and the creation of a supportive working environment.